KESUKSESAN IMPLEMENTASI SYSTEM APPLICATION PRODUCT (SAP) STUDI DI PT. SEMEN PADANG - Febryandhie Ananda; Rino Dwi Putra; Vito Shiga Hendrastyo (JURNAL PUNDI, 2017)
Mandal & Gunasekaran (2003) states that one of the resources that have become the ERP system is based on information technology, because it can increase the efficiency on the part of the company's operations. The aims of this study is to measure the success of user training variables and data analysis of System Application Product implementation in PT. Semen Padang. The method used is a sample survey and time for certain problems. The result is That user training and data analysis successfully support SAP implementation in PT. Semen Padang is categorized as successful with mean of User Training, Data Analysis and SAP Implementation are 4,31; 4,46; dan 4,46.